Single-Level Cervical Disc Replacement Using a PEEK-on-Ceramic Implant: Results of a Multicenter FDA IDE Trial With 24-Month Follow-up - Guyer, Richard D.; Coric, Domagoj; Nunley, Pierce D.; Sasso, Rick C.; Musacchio, Michael; Bae, Hyun W.; Peloza, John H.; Ohnmeiss, Donna D. (International journal of spine surgery, 2021)
Many early cervical total disc replacements (TDRs) produced motion through a ball-and-socket action, with metal endplates articulating with a plastic core. Polyetheretherketone (PEEK) is used increasingly for spinal implants due to its mechanical properties and lack of artifacts on imaging. A TDR was designed with titanium-coated PEEK endplates and a ceramic core. The purpose of this study was to compare this TDR with anterior cervical discectomy and fusion (ACDF) to treat single-level cervical disc degeneration.BACKGROUNDMany early cervical total disc replacements (TDRs) produced motion through a ball-and-socket action, with metal endplates articulating with a plastic core. Polyetheretherketone (PEEK) is used increasingly for spinal implants due to its mechanical properties and lack of artifacts on imaging. A TDR was designed with titanium-coated PEEK endplates and a ceramic core. The purpose of this study was to compare this TDR with anterior cervical discectomy and fusion (ACDF) to treat single-level cervical disc degeneration.This was a prospective, nonrandomized, historically controlled, multicenter US Food and Drug Administration (FDA) Investigational Device Exemption (IDE) trial. Patients received the PEEK-on-ceramic Simplify® Cervical Artificial Disc (n = 150). The historic control group included 117 propensity-matched ACDF patients from an earlier IDE trial. The primary outcome was a composite success classification at the 24-month follow-up. Outcome measures included the Neck Disability Index (NDI), neurological status, adverse events, subsequent surgery, a visual analog scale assessing neck and arm pain, and the Dysphagia Handicap Index. Radiographic assessment included flexion/extension range of motion and heterotopic ossification. Facet joints were assessed at 24 months using MRI.METHODSThis was a prospective, nonrandomized, historically controlled, multicenter US Food and Drug Administration (FDA) Investigational Device Exemption (IDE) trial. Patients received the PEEK-on-ceramic Simplify® Cervical Artificial Disc (n = 150). The historic control group included 117 propensity-matched ACDF patients from an earlier IDE trial. The primary outcome was a composite success classification at the 24-month follow-up. Outcome measures included the Neck Disability Index (NDI), neurological status, adverse events, subsequent surgery, a visual analog scale assessing neck and arm pain, and the Dysphagia Handicap Index. Radiographic assessment included flexion/extension range of motion and heterotopic ossification. Facet joints were assessed at 24 months using MRI.The success rate was significantly greater in the TDR group vs the ACDF group (93.0% vs 73.6%; P < .001). Mean NDI, neck pain, and arm pain scores improved significantly in both groups at all follow-up points. Mean NDI scores in the TDR group were significantly lower than ACDF scores at all follow-up points. There were no significant differences in the rates of serious adverse events. The range of motion of the TDR level had increased significantly by 3 months and remained so throughout follow-up. Facet joint assessment by MRI in the TDR group showed little change from preoperation.RESULTSThe success rate was significantly greater in the TDR group vs the ACDF group (93.0% vs 73.6%; P < .001). Mean NDI, neck pain, and arm pain scores improved significantly in both groups at all follow-up points. Mean NDI scores in the TDR group were significantly lower than ACDF scores at all follow-up points. There were no significant differences in the rates of serious adverse events. The range of motion of the TDR level had increased significantly by 3 months and remained so throughout follow-up. Facet joint assessment by MRI in the TDR group showed little change from preoperation.The TDR had an acceptable safety profile and a significantly greater composite success rate than ACDF. These results support that the PEEK-on-ceramic TDR is a viable alternative to ACDF for single-level symptomatic disc degeneration.CONCLUSIONSThe TDR had an acceptable safety profile and a significantly greater composite success rate than ACDF. These results support that the PEEK-on-ceramic TDR is a viable alternative to ACDF for single-level symptomatic disc degeneration.This study found that the PEEK-on-ceramic TDR is a viable treatment for symptoms related to cervical disc degeneration and offers similar or superior outcomes compared with fusion.CLINICAL RELEVANCEThis study found that the PEEK-on-ceramic TDR is a viable treatment for symptoms related to cervical disc degeneration and offers similar or superior outcomes compared with fusion.2.LEVEL OF EVIDENCE2.